Wireless soft implantable pressure sensors based on liquid metal with large-area mapping and adaptive implantation capabilities - Min-gu Kim; Pyungwoo Yeon; Sara Rachel Arussy Ruth; Jaeho Park; Jiancheng Lai; Donglai Zhong; Chengyi Xu; Jayoung Kim; Amin Arbabian; Paige M. Fox; Zhenan Bao (Proceedings of the National Academy of Sciences, 2026)
Innovations in soft materials have advanced the development of implantable devices for pressure monitoring, but fabrication and integration challenges remain, such as limited patterning resolution and poor scalability, hindering their miniaturization and wireless sensing capabilities. This study introduces methods and advantageous features of incorporating liquid metal into microfabriated, wireless soft implantable pressure sensors and wearable readout systems for large-area pressure mapping and adaptive implantation with autonomous folding and self-healing capabilities. Eutectic gallium–indium, a type of liquid metal, serves as both the deformable electrode for capacitive sensors and a low-resistance conductor for inductors. It is integrated into a thin-film, battery-free, inductive-capacitive wireless sensing platform. Scalable wireless sensor arrays are created through microfabrication for large-area pressure mapping. The wireless pressure sensor is also integrated with soft ferromagnetic and self-healing layers in cuff-type sensors to allow for autonomous folding in response to external magnets, eliminating the need for suturing. In addition, a miniaturized wearable readout system integrated into medical gloves enables wireless and real-time pressure monitoring. The presented wireless soft pressure-sensing method with large-area mapping and secure implantation capabilities offers alternatives to conventional medical tools for intraoperative monitoring and examinations.